2019
DOI: 10.21037/atm.2019.08.81
|View full text |Cite
|
Sign up to set email alerts
|

Increased cancer-specific mortality of very small size in carcinoembryonic antigen-elevated rectal cancer

Abstract: Background: The present study aimed to investigate the cause-specific survival (CSS) of very small rectal cancer in the context of preoperative serum carcinoembryonic antigen (CEA) elevation.Methods: Patients diagnosed with node-negative rectal cancer from the Surveillance, Epidemiology, and End Results (SEER) database from January 2004 to December 2010 meeting the inclusion criteria were identified for this study. The Cox proportional hazards regression analyses were conducted to identify independent factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several studies suggested that small size tumor had worse survival compared with large size tumor, if the TNM stage of CRC patients were similar. 19 - 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested that small size tumor had worse survival compared with large size tumor, if the TNM stage of CRC patients were similar. 19 - 23 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that small size tumor had worse survival compared with large size tumor, if the TNM stage of CRC patients were similar. [19][20][21][22][23] Our study also quantitatively analyzed risk factors related to TD and PNI status through bivariate logistic regression analysis. For TD, the most important risk factor was N stage.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Interestingly, several studies have also shown that patients with a smaller tumor size in pancreatic cancer, 7 breast cancer, 8 and certain T stage colon cancer [9][10][11][12][13][14][15][16] have a poorer prognosis, which is contrary to common knowledge; further, several studies have revealed an early spreading phenomenon of cancer cells. 15,[17][18][19][20] Most previous studies on tumor size were based on data extracted from open databases, 6,[9][10][11]13,15,16,21 which cannot be analyzed in depth owing to loss of information for several essential high-risk factors, such as lymphovascular invasion (LVI), perineural invasion (PNI), tumor deposit, BRAF or KRAS mutation, positive circumferential resection margin (CRM), and MMR status. The correlation between tumor size and these pathological features is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies on tumor size were based on data extracted from open databases, 6,9-11,13,15,16,21 which cannot be analyzed in depth owing to loss of information for several essential high-risk factors, such as lymphovascular invasion (LVI), perineural invasion (PNI), tumor deposit, BRAF or KRAS mutation, positive circumferential resection margin (CRM), and MMR status. The correlation between tumor size and these pathological features is still unclear.…”
Section: Introductionmentioning
confidence: 99%